Classical and contemporary readings in the philosophy of religion (Prentice-Hall, 1964)
This book is designed primarily for use in courses in philosophy of religion. Because such courses are sometimes arranged historically and sometimes in terms of topics or problems the material is presented here in two different tables of contents adapted to these two uses. The readings themselves are printed in chronological sequence, mainly in order that discussions by the same writer of different but related topics may conveniently be studied together- for example, Kant's critique of the three traditional theistic proofs.